2015
DOI: 10.1007/s11856-015-1210-8
|View full text |Cite
|
Sign up to set email alerts
|

On isomorphisms of Banach spaces of continuous functions

Abstract: We prove that if K and L are compact spaces and C(K) and C(L) are isomorphic as Banach spaces then K has a π-base consisting of open sets U such that U is a continuous image of some compact subspace of L. This sheds a new light on isomorphic classes of the spaces of the form C([0, 1] κ ) and spaces C(K) where K is Corson compact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…In fact, as it is explained in the final section, what is really crucial here is the continuity of the mapping L ∋ y → ||T * δ y ||. In a recent preprint [16] we were able to extend some of the results presented here to the case of arbitrary isomorphisms between spaces of continuous functions.…”
Section: Introductionmentioning
confidence: 63%
“…In fact, as it is explained in the final section, what is really crucial here is the continuity of the mapping L ∋ y → ||T * δ y ||. In a recent preprint [16] we were able to extend some of the results presented here to the case of arbitrary isomorphisms between spaces of continuous functions.…”
Section: Introductionmentioning
confidence: 63%
“…where quasi-open means that the image of every open set has nonempty interior (3.20). The second result is in fact a consequence of a study by G. Plebanek [39], however the proof of the first takes a considerable part of this paper. The possibility of obtaining these results is based on special properties of isomorphic embeddings and surjections.…”
Section: Introductionmentioning
confidence: 70%
“…13. An operator T : C(N * ) → C(N * ) is called fountainless or without fountains if, and only if, for every nowhere dense set F ⊆ N * the set In the following lemma we obtain a kind of left dual to an improvement of a theorem of Cengiz ("P" in [10]) obtained by Plebanek (Theorem 3.3. in [39]) which implies that if T is an isomorphic embedding then every x ∈ N * is in ϕ T (y) for some y ∈ N * .…”
Section: Local Behaviour Of Functions Associated With the Adjoint Opementioning
confidence: 99%
See 1 more Smart Citation
“…This result was improved by Galego and Rincn-Villamizar in [24], who showed that the same conclusion holds for Banach spaces not containing an isomorphic copy of c 0 . The way to this improvement was using a nice characterization of Banach spaces not containing an isomorphic copy of c 0 , see [35,Theorem 6.7], and a result of Plebanek, see [36,Theorem 3.3], which made it possible to remove the assumptions of separability and the Radon-Nikodym property. We prove an analogous result for closed subspaces of vector-valued continuous functions, whose Choquet boundaries consist of weak peak points.…”
Section: 2])mentioning
confidence: 99%